Effect of Photoneutrons on Thermalization Experiments in Deuterium - Gho, C. J.; Sbaffoni, M. M.; Parkinson, T. F.; Abbate, Máximo Julio (Taylor and Francis, 1980)
Fil: Gho, C. J. Comisión Nacional de Energía Atómica; Argentina